Study On the Influence of Training Methods on Track and Field Athletes’ Performance - Duan Mingtao, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The study undertakes a thorough review of the variables impacting the track and field athletes' unsatisfactory performance in an effort to improve their performance. It looks into how track and field athletes' training methods affect their physical performance. It also comes up with a way to measure their training progress and makes it easier to figure out how different factors affect their overall performance. Then, experiments are done to make sure that these results are true. This study also looks at the exact methods and approaches that track and field athletes use to train and improve their ability. The relationship between different training techniques and the performance outcomes in field events including the long jump, high jump, shot put, and javelin throw is carefully examined. This study tries to pinpoint the most efficient methods for realizing athletes' potential by examining the effects of various training strategies on their physical prowess, technique mastery, and overall performance. The suggested evaluation model is a useful tool for evaluating how well athletes' training programs are working. It considers a number of performance characteristics, such as technique precision, mental agility, strength, and endurance. Coaches and trainers can create training plans that are specific to each athlete's demands by a methodical analysis of these aspects, enhancing the way they perform on the field.